Implementation of Massive MIMO in 5G Networks: Strategy and Technical Studies in Indonesia - Ahmad Gani (Indonesian Journal of Advanced Research, 2023)
This study aims to examine the implementation of Massive MIMO (Multiple-Input Multiple-Output) in the 5G network and its implementation strategy in Indonesia. The methodology used includes literature study, field data analysis, and simulation. This study found that Massive MIMO can increase the capacity, speed, and spectrum efficiency of 5G networks. Implementation of this technology in Indonesia requires a strategy that includes optimizing infrastructure, regulation, and cooperation between stakeholders. The research results show that the implementation of Massive MIMO in the 5G network in Indonesia will provide significant benefits for users and the telecommunication industry. The conclusion drawn is that Massive MIMO is a key technology in developing 5G networks in Indonesia and needs full support from the government, operators, and related industries.